2022
DOI: 10.1177/13678779221092462
|View full text |Cite
|
Sign up to set email alerts
|

‘The filthy people’: Racism in digital spaces during Covid-19 in the context of South–South migration

Abstract: Notions of ‘race’ and disease are deeply imbricated across the globe. This article explores the historical, complex entanglements between ‘race’, disease, and dirtiness in the multicultural Chilean context of Covid-19. We conducted a quantitative content analysis and a discourse analysis of online readers’ comments (n = 1233) in a digital news platform surrounding a controversial news event to examine Chileans’ cultural representations of Haitian migrants and explore online racism and anti-immigrant discourse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…We were able to observe significant changes in different attitudinal dimensions, as an improvement in attitudes toward migrants in terms of conviviality and identity, and lower levels of threat during 2017 and 2018 (in reference to 2016) but with a prominent decay in conviviality and threat in the last survey wave (2021). These results are aligned with international and national studies that have shown that when societies face crises, people (and sometimes governments) tend to find scapegoats to blame, who are constructed as an "other" (Ahmad and Bradby, 2007;Cecchi, 2019;Bonhomme and Alfaro, 2022); in this case, LAC migrants. In that sense, Chileans would find it more difficult to live side by side with LAC migrants after times of crisis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We were able to observe significant changes in different attitudinal dimensions, as an improvement in attitudes toward migrants in terms of conviviality and identity, and lower levels of threat during 2017 and 2018 (in reference to 2016) but with a prominent decay in conviviality and threat in the last survey wave (2021). These results are aligned with international and national studies that have shown that when societies face crises, people (and sometimes governments) tend to find scapegoats to blame, who are constructed as an "other" (Ahmad and Bradby, 2007;Cecchi, 2019;Bonhomme and Alfaro, 2022); in this case, LAC migrants. In that sense, Chileans would find it more difficult to live side by side with LAC migrants after times of crisis.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, we found partial evidence supporting our fourth hypothesis, which proposed that those non-migrants with lower status and who interact more with migrants would also tend to increase their negative attitudes toward them. Coincidently to these results, other studies have shown that working-class Chileans reproduce, foremost, anti-indigenous and, secondly anti-black racism through everyday practices and interactions in order to claim a white or whiter racial identity compared to LAC migrants (Bonhomme, 2022 ) and that the pandemic has reinforced an anti-immigrant sentiment, whereby Chileans perceive migrants' everyday practices as a threat to Chilean identity and customs (Bonhomme and Alfaro, 2022 ). Such negative perceptions do not take into account that what non-migrants conceive as migrants' cultural practices, which shape their forms of inhabiting, are only the inevitable outcome of the precarious housing conditions in which they are forced to live (Bonhomme, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For Bonhomme and Alfaro (2022), the categories and their inferences continue to have a significant relevance for contemporary issues. In Latin American contexts, argues Wade (2010), Black peoples occupy a more ambiguous position in relation to native or indigenous peoples who were and continue to be "othered."…”
Section: Racialization and Colonialismmentioning
confidence: 99%
“…Othering occurs when “through sensorial perceptions, corporeal practices, and affective atmospheres, dichotomous borders are redrawn and enacted between ‘us’ and ‘them’” (Shaker Ardekani and Ahmadi, 2022, p. 4). As digital communities have formed as microcosms of the physical world, complete with similar power dynamics and embedded in larger social and cultural structures, recent research has identified enduring forms of discrimination which are perpetuated online, such as racist logic, “through which people construct imaginaries of racial superiority in digital spaces” (Bonhomme and Alfaro, 2022). Previous research has illustrated the detrimental impacts of othering in the online space, or “online othering,” which occurs in virtual spaces and in social media contexts and cultures, just as in physical spaces (Harmer and Lumsden, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%